Metastatic prostate tumor to testes: Sign of advance disease - Syed Adeel Ahmed; Muhammad Mubashir Nawaz; Yasir masood; Hina maqbool; Khurram Mir (Urology Case Reports, 2023)
Prostate cancer is the second most common cause of mortality for males in the United States. Metastases may be present, typically in the axial skeletal region. To date, few patients have presented with metastases to the testicles. We present the case of an adult male with diagnosed prostate cancer who presented and subsequently diagnosed bilateral testicular metastases. Testicular metastases secondary to diagnosed prostate cancer are very rare. Patients present with these metastases may have unfavorable prognosis. This case demonstrates that prostate cancer may metastasize to rare locations such as the testes, requiring further surgical intervention.